Mini Case Studies for Bone and Muscle Physiology - Kristin Hensley (Association of American Medical Colleges, 2010)
Abstract Introduction This module features a collection of short case studies concerning bone and muscle physiology that are suitable for first- or second-year anatomy and physiology students. The aim in creating and implementing the cases was to promote active and cooperative learning prior to students taking the bone and muscle physiology exam. The cases also help students to identify gaps in their knowledge prior the exam. Methods Each case assignment takes about 90 minutes over two class periods. Students are divided into small groups to work on a topic and then report out to different "expert" groups during the next class. Case topics include: endochondral ossification; the role of hormones in bone growth; the effect of aging on bone density; the dual roles of calcium; and the neural control of skeletal muscle. Results Currently, there is only circumstantial evidence for the effectiveness of the work. Based on student's active engagement and comments, students do enjoy the exercise, while learning both critical thinking skills and teamwork. For example, one student remarked that the case study was "awesome" and "entertaining," and asked me why we do not do case studies more often. Another student suggested doing one long case study over the course of the semester, adding more and more symptoms as they learn about new topics in lecture. Online case study discussion boards are frequented often outside of class. There is also a higher-than-average attendance rate on the days where case studies are presented. Discussion In future iterations, the effectiveness of this work will be investigated in more detail, with plans to conduct student evaluations to gather students' experiences and ideas about the case studies. Test scores may also be evaluated to study whether or not students perform better on case study material on the exam.